Inflammatory and Oxidative Stress Responses of Healthy Young Adults to Changes in Air Quality during the Beijing Olympics - Huang, W.; Wang, G. F.; Lu, S. E.; Kipen, H.; Y.D. Wang; Hu, M.; Lin, W. W.; Rich, D.; Ohman-Strickland, P.; Diehl, S. R.; Zhu, P.; Tong, J.; et al. (American Journal of Respiratory and Critical Care Medicine, 2012)
Rationale: Unprecedented pollution control actions during the Beijing Olympics provided a quasi-experimental opportunity to examine biologic responses to drastic changes in air pollution levels.Objectives: To determine whether changes in levels of biomarkers reflecting pulmonary inflammation and pulmonary and systemic oxidative stress were associated with changes in air pollution levels in healthy young adults.Methods: We measured fractional exhaled nitric oxide, a number of exhaled breath condensate markers (H+, nitrite, nitrate, and 8-isoprostane), and urinary 8-hydroxy-2-deoxyguanosine in 125 participants twice in each of the pre- (high pollution), during(low pollution), and post-Olympic (high pollution) periods. We measured concentrations of air pollutants near where the participants lived and worked. We used mixed-effects models to estimate changes in biomarker levels across the three periods and to examine whether changes in biomarker levels were associated with changes in pollutant concentrations, adjusting for meteorologic parameters.Measurements and Main Results: From the pre- to the during-Olympic period, we observed significant and often large decreases (ranging from -4.5% to -72.5%) in levels of all the biomarkers. From the during-Olympic to the post-Olympic period, we observed significant and larger increases (48-360%) in levels of these same biomarkers. Moreover, increased pollutant concentrations were consistently associated with statistically significant increases in biomarker levels.Conclusions: These findings support the important role of oxidative stress and that of pulmonary inflammation in mediating air pollution health effects. The findings demonstrate the utility of novel and noninvasive biomarkers in the general population consisting largely of healthy individuals.
Keywords: air pollution; ambient air; asthmatic-children; coronary-artery-disease; DNA-damage; exhaled breath condensate; heart-disease; inflammation; nitric-oxide; Oxidative Stress; particulate matter; pm2.5 exposure; pollution; respiratory health; the beijing olympics